PENGARUH INDUSTRI BESAR, SEDANG, KECIL TERHADAP PENYERAPAN TENAGA KERJA DI KOTA SURABAYA TAHUN 2018-2022 (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2024)
In Indonesia, the industrial sector is an important component of the economy, because it is a fairly high contributor to the country's foreign exchange, increases per capita income, and can expand employment opportunities thereby reducing the unemployment rate. With the large rate of population growth in the city of Surabaya, the industrial sector plays an important role in providing employment opportunities in the city of Surabaya, followed by equal distribution and improving the quality of human resources. The aim of this research is to determine the influence of the amount of capital in large industries, medium industries and small industries on labor absorption in the city of Surabaya. This research uses a quantitative approach and the data used is 5 (five) year time series data starting from 2018-2022 obtained from BPS Surabaya City, data collection using documentation methods, as well as analysis tools in the form of multiple linear regression using the Cobb-production function. Douglas uses SPSS. The results of this research show that the results of the F test simultaneously have a significant effect on the capital variables of large industry (X1), medium industry (X2), and small industry (X3) on labor absorption (Y). The results of the t test on the large industrial capital variable (X1) and small industrial capital (X3) partially have a significant effect on labor absorption, while the medium industrial capital variable (X2) partially has no effect on labor absorption (Y)